Students’ Thesis Statement in Essay Writing Class - Wijaya, M. Sayid (English Education: Jurnal Tadris Bahasa Inggris, 2017)
Writing an essay is quite tricky since it needs more than pouring all ideas in written form. Those ideas must be organized well since different essays were structured in different ways. However, the core of an essay lies in its thesis statement. It is the answer of the topic question, in which the construction of the rest parts of the essay was dependable on it. Therefore, it is imperative that the students accurately determine correct and focused thesis statement so that their essay will be a good one. Thus, this article tried to analyze students’ thesis statement and the possible causes to not good thesis statement. The results of analysis revealed that students’ thesis statement could be categorized into good thesis statement, good thesis statement with some focus, good thesis statement with too broad focus, quite good thesis statement, and not good thesis statement. The possible causes that emerged and influenced students’ thesis statement were students’ grammatical mastery level and their topical knowledge.